On the diversity of accommodation mechanisms in the tribology of Bulk Metallic Glasses. (January 2020) - Cornuault, Pierre-Henri; Colas, Guillaume; Lenain, Alexis; Daudin, Rémi; Gravier, Sébastien
Abstract: Bulk Metallic Glasses (BMG) have exceptional mechanical properties compared to their traditional crystalline counterparts. However, BMGs often exhibit scattered tribological behaviours. To better understand the underlying mechanisms governing the behaviour of BMGs, four different alloys (Zr52.5 Ti5 Cu17.9 Ni14.6 Al10, Cu47 Zr46 Al7, Cu60 Zr33 Ti7, and Ni62 Nb33 Zr5 ) were studied in pure sliding, reciprocating conditions. The study shows that the residual elements coming either from the counterpart or the surrounding environment plays a major role in their tribological behaviour. The composition of the BMG have a lower impact in the process. Eventually, the study concludes that optimization of the tribological behaviour of the BMGs might not necessarily rely on optimizing BMG composition but might rather rely on optimizing the choice of counterparts as a function of contact conditions. Highlights: Tribochemistry plays a major role in the tribological behaviour of metallic glasses. Deterministic impact of residual elements stemming from the counterpart and the environment. Ni62 Nb33 Zr5 BMG demonstrated as a good candidate for tribological applications1.